2023
DOI: 10.1007/s10578-023-01582-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status, Protective Factors, and Mental Health Problems in Transition from Adolescence to Emerging Adulthood: Results of the Longitudinal BELLA Study

Jenny Maurer,
Ann-Katrin Meyrose,
Anne Kaman
et al.

Abstract: Lower familial socioeconomic status (SES) is associated with more mental health problems in adolescence. The aim of this study was to identify factors that may protect adolescents from families with lower SES from developing mental health problems in emerging adulthood. Data of the population-based longitudinal BELLA study included n = 426 participants aged 13 to 17 years at t0 (2009–2012) and 18 to 24 years at t1 (2014–2017). Hierarchical multiple linear regressions with interaction terms were conducted, exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A supportive family environment, however, can mitigate mental health challenges, irrespective of socioeconomic status. A longitudinal study included 426 adolescents revealed that self-efficacy exhibited a modest protective effect against mental health problems in those belonging to low-income homes, while social support showed a similar effect for adolescents from higher-income families [16]. Additionally, a positive family environment emerged as a factor associated with lower mental health problems in adolescence, irrespective of socioeconomic status.…”
Section: Socioeconomic Aspect and Mental Healthmentioning
confidence: 99%
“…A supportive family environment, however, can mitigate mental health challenges, irrespective of socioeconomic status. A longitudinal study included 426 adolescents revealed that self-efficacy exhibited a modest protective effect against mental health problems in those belonging to low-income homes, while social support showed a similar effect for adolescents from higher-income families [16]. Additionally, a positive family environment emerged as a factor associated with lower mental health problems in adolescence, irrespective of socioeconomic status.…”
Section: Socioeconomic Aspect and Mental Healthmentioning
confidence: 99%